2007
DOI: 10.1097/rli.0b013e3181238330
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction and Visualization of Fiber and Laminar Structure in the Normal Human Heart from Ex Vivo Diffusion Tensor Magnetic Resonance Imaging (DTMRI) Data

Abstract: A visualization algorithm was developed to demonstrate the complex 3-dimensional orientation of the fibers and sheets in human myocardium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
147
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(152 citation statements)
references
References 40 publications
4
147
0
Order By: Relevance
“…The availability of a full 3D atlas of the cardiac architecture opens the door to not only the construction of more accurate extrapolation models for in vivo acquisitions, but also to a better understanding of various cardiac mechanical functions, cardiac electrophysiology patterns, and remodeling processes. So far only ex vivo canine DT-MRI studies [9,13] have been considered, and in humans, only cases using a single ex vivo heart has been studied [15] and visualized in 3D [16]. Histological and DT-MRI studies all lead to similar findings.…”
Section: Introductionmentioning
confidence: 51%
“…The availability of a full 3D atlas of the cardiac architecture opens the door to not only the construction of more accurate extrapolation models for in vivo acquisitions, but also to a better understanding of various cardiac mechanical functions, cardiac electrophysiology patterns, and remodeling processes. So far only ex vivo canine DT-MRI studies [9,13] have been considered, and in humans, only cases using a single ex vivo heart has been studied [15] and visualized in 3D [16]. Histological and DT-MRI studies all lead to similar findings.…”
Section: Introductionmentioning
confidence: 51%
“…The overall scheme of left-handed helical patterns in the epicardial regions of the left ventricular walls, and reciprocal right-handed helical patterns in the endocardial regions, have been known since the stellar study of Pettigrew (Pettigrew, 1864). This architectural outline was revived by Streeter using histology (Streeter et al, 1966;Streeter et al, 1969), and has recently been fully consolidated using the technique of diffusion tensor magnetic resonance imaging (Helm et al, 2005;Rohmer et al, 2007). Using this novel, but validated, technique (Hsu et al, 1998;Scollan et al, 1998), we have now demonstrated that in keeping with the demonstration of myocytes also aggregated in transmural fashion (Lunkenheimer et al, 2006), reproducible pathways can be demonstrated within the walls using diffusion tensor magnetic resonance imaging (Smerup et al, 2008).…”
mentioning
confidence: 99%
“…These studies demonstrate salient and consistent local and global patterns in mammalian cardiac fiber architecture. These patterns are supported by histological measurements [1] and include [6] an inner to outer wall turning of the cardiac fibers in a smooth and regular fashion undergoing a total change of about 110…”
Section: Introductionmentioning
confidence: 68%
“…Diffusion Tensor Imaging (DTI) of ex-vivo hearts has been studied extensively across many species, including the human [1], dog [2], goat [3], rat [4] and the pig [5]. These studies demonstrate salient and consistent local and global patterns in mammalian cardiac fiber architecture.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation